Democratic Republic of Timor-Leste : 2011 Article IV Consultation: Staff Report; Informational Annex; Debt Sustainability Analysis; and Public Information Notice. (IMF Staff Country Reports; Country Report ;, 2012)
Timor-Leste has made substantial progress toward restoring stability and rebuilding the country after emerging from a long struggle for independence and internal conflicts between 1999 and 2006. The government has launched its Strategic Development Plan to step up development. A well-managed Petroleum Fund is in place, and new institutions have been established to manage large public investment programs. The authorities need to further strengthen institutional capacities and develop human resources. Developing the financial sector and strengthening the credit culture are crucial for sustained growth in the private sector.